2017
DOI: 10.1002/mp.12695
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of 90Y‐SPECT/CT self‐calibration approaches on the quantification of voxel‐level absorbed doses following 90Y‐microsphere selective internal radiation therapy

Abstract: The mean error of < 3% for commercial software can be considered clinically acceptable for Y-SIRT dosimetry. Absorbed dose quantification using Y-SPECT self-calibration with the chest-abdomen contour was equivalent to that calculated using the SPECT FOV, but self-calibration with the total liver contour yielded substantially higher (~70%) dose values. The large biases revealed by our study suggest that consistent absorbed dose calculation approaches are essential when comparing Y-SIRT dosimetry between differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 18 publications
2
24
0
1
Order By: Relevance
“…The details of this method and its benchmarking against other voxelized dose calculations, such as kernelbased methods and Monte Carlo computations, have been published previously. 6,8,9 As discussed above and previously, 6,24 90 Y-Sureplan uses a self-calibration to obtain quantitative SPECT/CT images with SPECT activity concentration in each voxel (Bq/mL instead of counts/mL). The liver volume was chosen for this self-calibration due to the fact that most counts outside the liver volume are likely erroneous artifacts of SPECT reconstruction and difficulty in 90 Y bremsstrahlung scatter correction.…”
Section: G Voxel Dosimetry: Maa and 90 Ymentioning
confidence: 99%
See 1 more Smart Citation
“…The details of this method and its benchmarking against other voxelized dose calculations, such as kernelbased methods and Monte Carlo computations, have been published previously. 6,8,9 As discussed above and previously, 6,24 90 Y-Sureplan uses a self-calibration to obtain quantitative SPECT/CT images with SPECT activity concentration in each voxel (Bq/mL instead of counts/mL). The liver volume was chosen for this self-calibration due to the fact that most counts outside the liver volume are likely erroneous artifacts of SPECT reconstruction and difficulty in 90 Y bremsstrahlung scatter correction.…”
Section: G Voxel Dosimetry: Maa and 90 Ymentioning
confidence: 99%
“…The two commonly used dosimetry models that improve upon MIRD are the partition model (PM) [4][5][6] and voxel dosimetry. [7][8][9][10][11] The imaging modalities primarily used for 90 Y SIRT dosimetry are 99m Tc-macroaggregated albumin (MAA) single photon emission computed tomography/CT (SPECT/CT) for treatment planning 10 and 90 Y-SPECT/CT 7 or 90 Y-positron emission tomography/CT (PET/CT) 11 for treatment verification. It has previously been reported that differences may exist between either planning (MAA) and treatment ( 90 Y) images or 90 Y-SPECT and 90 Y-PET that can lead to differences in dose calculation.…”
Section: Introductionmentioning
confidence: 99%
“…This method avoids counts due to image artifacts. The motivation for using directly the patients’ liver uptake to calculate the CF is that due to the proximity of the treatment to the target area where the 90 Y microspheres are deposited predominantly in the liver, the 90 Y activity can be determined with high accuracy . Calibration curves were generated using linear regression analysis to derive the relationship between patient administered activity and reconstructed counts.…”
Section: Methodsmentioning
confidence: 99%
“…LDM users argue that the image voxel size and point spread function (PSF) of the imaging system provide enough spatial blurring of the image to represent the dose spread of the β ‐ from 90 Y, and therefore, convolution with a DPK is unnecessary . Balagopal and Kappadath recently validated the LDM option of MIM SurePlan™ with 90 Y SPECT images against Monte Carlo simulations . In this study, we compared results from the voxel S value option of this commercial dosimetry software — MIM SurePlan™ LiverY90 (MIM Software, Inc., Cleveland, OH) — to a MATLAB‐based algorithm developed in‐house for the purpose of commissioning the commercial software for clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…10 Balagopal and Kappadath recently validated the LDM option of MIM SurePlan TM with 90 Y SPECT images against Monte Carlo simulations. 22 In this study, we compared results from the voxel S value option of this commercial dosimetry software -MIM SurePlan TM LiverY90 (MIM Software, Inc., Cleveland, OH)to a MATLAB-based algorithm developed in-house for the purpose of commissioning the commercial software for clinical use.…”
Section: Introductionmentioning
confidence: 99%